2017
DOI: 10.2176/nmc.oa.2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection after Malignant Brain Tumor Resection: A Multicenter Study for Induction of a Basic Care Bundle

Abstract: Patients with malignant brain tumors are possibly at increased risk for surgical site infections (SSIs) considering the various medical situations associated with the disease. However, the actual rate of SSI after malignant brain tumor resection has not been well established, despite the potential impact of SSI on patient outcome. To investigate the incidence of SSI following malignant brain tumor surgery, we performed a retrospective study in 3 neurosurgical units. Subsequently, aiming at the reduction of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
1
20
1
Order By: Relevance
“…etc. but the most commonly isolated organism was S. aureus (30). Separate studies by Rolston et al, Bhat et al, and Uzuka et al also confirmed these findings.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…etc. but the most commonly isolated organism was S. aureus (30). Separate studies by Rolston et al, Bhat et al, and Uzuka et al also confirmed these findings.…”
Section: Discussionmentioning
confidence: 76%
“…Separate studies by Rolston et al, Bhat et al, and Uzuka et al also confirmed these findings. 22,29,30 High prevalence of S. aureus may be due to its distribution in the human body. Other normal flora like E. coli, K. pneumoniae, Citrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Uzuka T et. al [ 13 ] reported no significant difference in the frequency of surgical site infection (SSI) between supratentorial and infratentorial malignant brain tumor. This study, however, may have been underpowered as we found a significantly higher incidence of S/SS in our infratentorial tumor group when compared to the supratentorial tumor group ( p = 0.0019).…”
Section: Discussionmentioning
confidence: 99%
“…This study strengthens the knowledge that various risk factors are associated with the development of SSIs, with few of these risk factors being modifiable. Smoking, diabetes, operative duration and perioperative dexamethasone have all been shown to inhibit satisfactory wound healing, 1,5,9 which could in turn lead to wound leaks.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Surgical site infections (SSIs) are of profound significance in a healthcare setting, both in terms of patient outcomes and healthcare costs. SSI rates have been described in the literature as accounting for 1.1-19.78% of all healthcare associated infections 1 and they create an additional cost to the National Health Service (NHS) of £2,100-£10,500 per infected case. 2 The need for further surgical intervention to treat SSIs increases this cost owing to extended postoperative hospital stays, prolonged intravenous antibiotic treatment, delayed wound healing and extended inpatient rehabilitation times.…”
mentioning
confidence: 99%